Análise comparativa dos desfechos clínicos de pacientes após parada cardiorrespiratória: Um estudo de dupla-coorte - Coelho, Débora Costa Gomes (2024)
Introduction: adult cardiopulmonary arrest (CPA) is a serious clinical emergency that continues to have low survival rates. The post-CPA prognosis of non-critically ill patients is influenced by failure to recognize clinical deterioration early, as well as a lack of professionals trained in cardiopulmonary resuscitation (CPR) maneuvers. Given this long-standing public health problem, this study is important because it is essential to understand the effects of CPR techniques and identify areas for improvement, with the aim of improving survival and quality of life for post-CPA patients, with a direct impact on care and clinical outcomes. Objective: to evaluate the clinical outcomes of non-critically ill patients after an in-hospital CPR training program for nursing professionals. Material and Methods: this is an integrated observational double-cohort study, comprising a retrospective cohort and a prospective cohort, covering the period from January 2022 to October 2023. Each cohort involved different times and different patients, totaling 137 retrospective and 41 prospective, with a 1:3 ratio. The population was made up of non-critical patients who had suffered a CPA. The research was conducted in non-critical care units of two hospitals in Sergipe, with data collected from medical records using an instrument specifically designed for this study. Clinical outcomes were compared between the two cohorts using Fisher's exact test and survival curves using the log-rank test, with a significance level of 5%. The primary outcomes included the success rate of CPR maneuvers and survival at 30 days. Secondary outcomes were the number of CPR recurrences and favorable neurological status assessed by the Cerebral Performance Category (CPC) score in the first 24 hours, after 30 days and at hospital discharge. Results: the majority of patients who suffered CPA progressed to death (91.2% vs. 90.2%, p=0.765). However, at the prospective time point, there was a lower mortality rate during CPA (65% vs. 46.3%, p=0.044), there was an improvement in the rate of Return of Spontaneous Circulation (RSC) and no further CPA within one hour (21.2% vs. 46.3%, p=0.002), besides a higher incidence of transfer to Intensive Care Unit (ICU) post-CPA (24.3% vs. 46.3%, p=0.01). Of the patients who responded to CPR, good adult cerebral performance (CPC 1-2) was seen after 30 days of CPR (8.3% vs. 50%; p=0.004) in the prospective cohort. However, it was not possible to observe a difference between the survival curves and the rate of PCR recurrences. Conclusion: these findings demonstrate that the use of a CPR training program has a positive impact on the clinical outcomes of non-critically ill patients. There was less mortality during CPA, a higher rate of RSC and no further CPA within one hour and, consequently, a higher incidence of post-CPA ICU transfer in the non-critical care unit in the prospective cohort. There was a lower incidence of unfavorable neurological outcomes in the prospective cohort.